Children’s Moral Development: Rationality or Empathy? - Chen, Xi (Pedagogika Społeczna Nova, 2025)
In what ways should children be nurtured with rationality? This article makes inquiry into this topic. Following an opening paragraph of an anecdote, the author traces a general history of theories embedded in the lieu of children’s development of morals. There engenders two main theoretical approaches of moral development as the children grow and develop: rationality and empathy. It is in a long standing debates whether children’s morals induced from rational development or whether they blooming from empathy experiences. The author examines theoretical tracks of these two approaches (rationality and empathy) ,and the author argues that morality of children should be developed by cultivating both children’s rationality and their empathy.